2012
DOI: 10.1007/s00114-012-0976-3
|View full text |Cite
|
Sign up to set email alerts
|

Japanese Papilio butterflies puddle using Na+ detected by contact chemosensilla in the proboscis

Abstract: Many butterflies acquire nutrients from non-nectar sources such as puddles. To better understand how male Papilio butterflies identify suitable sites for puddling, we used behavioral and electrophysiological methods to examine the responses of Japanese Papilio butterflies to Na+, K+, Ca2+, and Mg2+. Based on behavioral analyses, these butterflies preferred a 10-mM Na+ solution to K+, Ca2+, and Mg2+ solutions of the same concentration and among a tested range of 1 mM to 1 M NaCl. We also measured the ion concen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 15 publications
(27 reference statements)
1
12
0
Order By: Relevance
“…We already see evidence of altered foraging behavior in some species-ants that live closer to roads forage less actively for sodium than those farther from the road (36), and moose also show some preference for roadside ponds because of salt runoff (35). Given that butterflies and moths can detect sodium concentration through contact chemoreceptors (62,63), it is possible that they are also showing changes in foraging behavior. This observation raises the question of whether a thirst for a micronutrient, such as sodium, could lead to increased preference for roadside habitats.…”
Section: Implications: Changes In Limited Nutrients and Selection On mentioning
confidence: 95%
“…We already see evidence of altered foraging behavior in some species-ants that live closer to roads forage less actively for sodium than those farther from the road (36), and moose also show some preference for roadside ponds because of salt runoff (35). Given that butterflies and moths can detect sodium concentration through contact chemoreceptors (62,63), it is possible that they are also showing changes in foraging behavior. This observation raises the question of whether a thirst for a micronutrient, such as sodium, could lead to increased preference for roadside habitats.…”
Section: Implications: Changes In Limited Nutrients and Selection On mentioning
confidence: 95%
“…The fluid samples were stored at -20°C until analysis. As described in [ 5 ], the fluid samples were analyzed with ion chromatography using a PU2080i solvent delivery pump (JASCO, Tokyo, Japan), a JASCO CO-2060 column oven, a CD-5 conductometric detector (Shodex, Kawasaki, Japan), and a JASCO DG-2080-53 online degasser. The separations were achieved on a 4.6-mm ID × 125-mm length fused silica gel column coated with a carboxylic polymer (Shodex IC Y-421) using a guard column (Shodex IC YK-G).…”
Section: Methodsmentioning
confidence: 99%
“…Previous research has shown that the taste of Na + induces puddling in Papilio glaucus in North America [ 1 ]; Pieris rapae in North America [ 2 ]; Papilio helenus and P . memnon in Borneo, Malaysia [ 3 ]; one of the Papilio machaon group of species in North America [ 4 ]; and in all the Papilio species on the main islands of Japan [ 5 ]. The transference of Na + from male butterflies to females during mating has also been observed [ 6 10 ]; hence, it has been suggested that the purpose of puddling is to absorb Na + to enhance fertility.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations